EFFICIENT DESIGN OF CONICAL DOUBLE DRUM SEPARATOR FOR SEPARATING COTTON SEED RUSHANKA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article provides an analysis of the design features of separators for separating cottonseed rushanka, recommends a design scheme and the principle of operation of an effective two-drum separator for separating cottonseed rushanka.